2019
DOI: 10.5114/jcb.2019.84537
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for salvage treatment of non-small-cell lung cancer: percutaneous CT fluoroscopy-guided permanent seed brachytherapy for salvage treatment of lung cancer: long-term results of a case series

Abstract: Purpose We sought a curative technique to treat recurrent or primary non-small cell lung cancer (NSCLC) with a minimally invasive outpatient technique that could be repeated multiple times, had minimal pulmonary toxicity, and was readily available in the community setting. Percutaneous outpatient computed tomography (CT) fluoroscopy-guided permanent seed brachytherapy fits these criteria. Material and methods Eight lesions in five patients (three patients had two lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Moreover, a placement with stent re-stenosis offers limited survival benefits in the absence of locoregional therapy for endobronchial lesions. Recently, a novel therapy with 125 I seed was developed and exhibited promising outcomes in lung cancer [ 10 , 12 , 13 ]. In the present study, we also confirmed that CT-guided 125 I implantation was safe and efficient in MAC patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a placement with stent re-stenosis offers limited survival benefits in the absence of locoregional therapy for endobronchial lesions. Recently, a novel therapy with 125 I seed was developed and exhibited promising outcomes in lung cancer [ 10 , 12 , 13 ]. In the present study, we also confirmed that CT-guided 125 I implantation was safe and efficient in MAC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the choice of therapy was based on the type and location of airway stenosis, pulmonary function, comorbidities, previous treatments, and life expectancy. Recently, 125 I radioactive seed implantation had proved its efficacy in various malignant tumors [10,11,12,13]. The results of Lu et al revealed that trans-bronchoscopy 125 I radioactive seed implantation brachytherapy could improve the survival and quality of life of patients with pulmonary atelectasis induced by intralumi-nal airway obstruction [14].…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…In early-stage lung cancers that are not suitable for surgical resection or EBRT, LDR-SABT could be used as an alternative anti-cancer treatment with interstitial radioactive seed implantation and image guidance [ 27 , 29 ]. The prescription dose of radioactive seed was generally 100–120 Gy in lung cancer studies [ 6 , 42 , 77 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. Another study reported that the local cancer control rate was 80–100% with promising 1- and 2-year survival rates (90–95% and 70–80%, respectively) for early-stage lung cancer [ 27 ].…”
Section: The Practice Of Sabt: Outcomes Advances and Perspectivesmentioning
confidence: 99%
“…Subsequent to our initial experience with treatment of recurrent non-small cell lung cancer (NSCLC) with computed tomography (CT)-guided 103 Pd permanent seed brachytherapy (CTGPSB) [7], we have had a high-volume community hospital experience with multiple pulmonary metastatic ACC lesions utilizing CTGPSB, and here, present a part of the data showing that multiple pulmonary metastases can be rapidly, safely, and effectively treated.…”
Section: Purposementioning
confidence: 99%